2008
DOI: 10.1074/jbc.m708703200
|View full text |Cite
|
Sign up to set email alerts
|

Hsf-1 and POB1 Induce Drug Sensitivity and Apoptosis by Inhibiting Ralbp1

Abstract: Hsf-1 (heat shock factor-1) is a transcription factor that is known to regulate cellular heat shock response through its binding with the multispecific transporter protein, Ralbp1. Results of present studies demonstrate that Hsf-1 causes specific and saturable inhibition of the transport activity of Ralbp1 and that the combination of Hsf-1 and POB1 causes nearly complete inhibition through specific bindings with Ralbp1. Augmentation of cellular levels of Hsf-1 and POB1 caused dramatic apoptosis in non-small ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(103 citation statements)
references
References 41 publications
5
98
0
Order By: Relevance
“…Hsf-1 also causes specific and saturable inhibition of the transport activity of RalBP1. The combined augmentation of Hsf-1 and REPS2/POB1 causes nearly complete inhibition of RalBP1 and a dramatic apoptosis in NSLC (non-small cell lung cancer) cell line H358 through Ralbp1 binding (Singhal et al, 2008). The marked apoptotic effect caused by the increase of Hsf-1 and REPS2/POB1 in lung cancer cells, suggests a novel targeted therapy in which liposomally encapsulated Hsf-1 and POB1 could be used clinically as a therapeutic agent.…”
Section: Implicated Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Hsf-1 also causes specific and saturable inhibition of the transport activity of RalBP1. The combined augmentation of Hsf-1 and REPS2/POB1 causes nearly complete inhibition of RalBP1 and a dramatic apoptosis in NSLC (non-small cell lung cancer) cell line H358 through Ralbp1 binding (Singhal et al, 2008). The marked apoptotic effect caused by the increase of Hsf-1 and REPS2/POB1 in lung cancer cells, suggests a novel targeted therapy in which liposomally encapsulated Hsf-1 and POB1 could be used clinically as a therapeutic agent.…”
Section: Implicated Inmentioning
confidence: 99%
“…Shingal et al show a ternary complex formation between RalBP1, Hsf-1, and REPS2/POB1. RalBP1, Hsf1, HSP90 and tubulin make a complex in cell (Singhal et al, 2008). Hsf-1 and REPS2/POB1 induce drug sensitivity and apoptosis by inhibiting RalBP1.…”
Section: Implicated Inmentioning
confidence: 99%
“…1B). These structural features link RLIP76 to a confounding array of physiological functions including clathrin-coated-pit-mediated receptor-ligand endocytosis of epidermal growth factor receptor (EGFR), insulin receptor (IR) and transforming growth factor ß (TGF-ß) as well as mitosis signaling (8,16,(21)(22)(23)(24)(25)(26)(27). In a series of experiments over the last decade, an important role for RLIP76 in malignant cell survival and drug resistance and normal tissue response to oxidative stress has been confirmed.…”
Section: Rlip76: a Non-abc Transportermentioning
confidence: 99%
“…Recently, it has been shown that overexpression of REPS2 and its binding with RalBP1 induce apoptosis and loss of REPS2 expression results in dysregulation of growth factor signaling in prostate cancer cells (Oosterhoff et al, 2003;Oosterhoff et al, 2005). Likewise, augmentation of cellular levels of REPS2 and Hsf-1 result in dramatic apoptosis in non-small cell lung cancer cell line H358 through RalBP1 inhibition (Singhal et al, 2008). What is more, the binding of REPS2 to PAG2 inhibits cell migration (Oshiro et al, 2002).…”
mentioning
confidence: 99%